Interior point method for long-term generation scheduling of large-scale hydrothermal systems - Azevedo, Anibal Tavares [UNESP]; Leite Oliveira, Aurelio Ribeiro; Soares, Secundino (Springer, 2009)
This paper presents an interior point method for the long-term generation scheduling of large-scale hydrothermal systems. The problem is formulated as a nonlinear programming one due to the nonlinear representation of hydropower production and thermal fuel cost functions. Sparsity exploitation techniques and an heuristic procedure for computing the interior point method search directions have been developed. Numerical tests in case studies with systems of different dimensions and inflow scenarios have been carried out in order to evaluate the proposed method. Three systems were tested, with the largest being the Brazilian hydropower system with 74 hydro plants distributed in several cascades. Results show that the proposed method is an efficient and robust tool for solving the long-term generation scheduling problem.
Keywords: Hydrothermal generation scheduling; Long-term operational planning; Nonlinear optimization; Interior point method